(untitled) (Texas Journal of Engineering and Technology, 2022)
The article considers the principles of operation of electro-optical Mach–Zehnder modulators. Methods for transferring the received microwave radiation of the tested radar to the optical carrier frequency are presented. Connection schemes and modulation formats are given